Perbandingan Hyouka dalam Versi Novel dan Film - Saputri, Dina Septiani (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2024)
The tittle of this research is “The Comparasion between Novel and Movie of Hyouka”. The purpose is to find the ecranization process that occurs between the novel Hyouka by Honobu Yonezawa and the movie Hyouka by Mari Asato. The method used is descriptive qualitative and the theory of ecranization from Pamusuk Eneste, the data collection technique is observing notes, and the data analysis technique uses descriptive analysis techniques. From the results of this study found some data on the process of ecranization that occurs, namely fifteen data of shrinkage, ten data of addition and eleven data of variation changes. The ecranization process occurs in the intrinsic elements which include the shrinking and changing variations in the plot, shrinking, adding and changing variations in the characters, as well as shrinking and changing variations in the setting. In addition, it was also concluded based on the similarities and differences after comparing Hyouka in the novel and film versions, it was found that the film director was considered less successful in adapting the novel to the film field because there were many differences in the intrinsic elements of characterization.